Early mobilization and length of wound healing post-sectio caesarean: A cross-sectional study - Yulianti, Lisa; Yunita, Laurensia; Mariana, Frani; Palimbo, Adriana (Health Sciences International Journal, 2024)
Background: Mobilization post sectio caesarean is an effort to prevent risk and complications of infection. The early mobilization stages are the first hour after surgery, lie down first, move the arms, bend and slide the legs, and lift the heels, six to ten hours after surgery woman is required to turn her body to the right and left side. Objective: To determine the correlation between early mobilization with length of wound healing post-sectio caesarean. Method: A quantitative analytical study with a cross-sectional approach. The study included 30 women who had had a caesarean from September to November 2023. The research instruments used were a questionnaire and an early mobilization observation sheet. Wound healing was measured by means of the REEDA scale. Chi-square test for statistical analysis. Results: The results showed that there were 22 respondents in good category 73.3%, and 27 people in fast wound healing category 90%. The chi-square test obtained a p-value of 0.014, it was mean that there was a significant relationship between early mobilization and length of wound healing post-sectio caesarean. Conclusion: The application of early mobilization is effective in overcoming physical mobility disorders so that women post-sectio caesarean can return to their activities.